English biography in the seventeenth century : a critical survey - Pritchard, Allan (University of Toronto Press, 2005)
"Although biography is one of today's most flourishing literary genres, its early history has attracted much less attention than that of other forms, a neglect that is especially apparent in the case of the formative period of English biography, the seventeenth century. This new work by Allan Pritchard fills the scholarly void by providing a wide-ranging and comprehensive survey of this period's biographical writings."